PENGARUH PENAMBAHAN BERBAGAI KADAR PISANG DAN UBI JALAR PADA PERTUMBUHAN KULTUR TIGA JENIS PHALAENOPSIS - Garvita, Raden Vitri; Handini, Elizabeth (Buletin Kebun Raya, 2011)
The aim of the experiment was to determine the effect of organic materials on the growth of Phalaenopsis zebrina, P. Â javanica and P. Â fuscata explants without rootsÂ  in Knudsonâs C medium with additional of coconut water. Â Observation were conducted for 10 months and the data were analyzed by ANOVA. The result showed that the survival ability of P. zebrina and P. javanica were only 3 months in KC medium with additional of coconut water (150 g/l), banana (50 g/l) and sweet potatoes (20 g/l), while P. fuscata grew further up to 10 months in all media. Additional of organic material: 150 g/l coconut water, 25 g/l banana and 15 g/l sweet potatoes in KC medium gave the best result on increasing the leaf and the shoot numbers, while additional of 150 g/l coconut water, 50 g/l banana and 20 g/l sweet potatoes to KC medium only increasing theÂ  root number of P. fuscata.